Ionospherically reflected proton whistlers. Issue 12 (19th December 2014) - Vavilov, D. I.; Shklyar, D. R.
Abstract: We present experimental observations and detailed investigation of the variety of proton whistlers that includes transequatorial and ionospherically reflected proton whistlers. The latter have previously been indicated from numerical modeling of spectrograms. The study is based on six‐component ELF wave data from the Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions (DEMETER) satellite which permits to obtain not only spectrograms displaying the power spectral density but also such wave properties as the polarization, wave normal angle, wave refractive index, and normalized parallel component of the Poynting vector. The explanation of various types of proton whistlers is based on the properties of ion cyclotron wave propagation in a multicomponent magnetoplasma, with special consideration of the effect of ion hybrid resonance reflection. Analysis of experimental data is supplemented by numerical modeling of spectrograms that reproduces the main features of experimental ones. As a self‐contained result, we provide conclusive experimental evidences that the region illuminated by a lightning stroke in the Earth‐ionosphere waveguide may spread over a distance of 4000 km in both hemispheres. Key Points: First experimental observation of ionospherically reflected proton whistlers Estimation of lightning‐illuminated region in the Earth‐ionosphere waveguide Detailed study of ion hybrid resonance reflection for proton‐cyclotron waves